Tingkat Pengetahuan Siswa terhadap Pembelajaran Atletik di MAN 1 Bekasi pada Masa Pandemi Covid-19 - Ahmad Fauzi Abdurrahman; Rekha Ratri Julianti; Rahmat Iqbal (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine how high the level of knowledge of class XI students towards athletic learning at MAN 1 Bekasi City. This research is a quantitative descriptive. The method used in this study is a survey method, the instrument is multiple choice, the subjects in this study were students of class X MAN 1 Bekasi City, totaling 60 people. The data analysis technique used quantitative descriptive analysis as outlined in the percentage. The results of this study indicate that the level of knowledge of class X students towards athletic learning is in the categories of "very low" 12%, "low" 10%, "moderate" 43%, "high" 35%, and "very high" 0%.